Individual Differences in Moral Development: Does Intelligence Really Affect Children’s Moral Reasoning and Moral Emotions? - Beißert, Hanna M.; Hasselhorn, Marcus (Frontiers in Psychology, 2016)
This study investigates the relationship between intelligence and individual differences in children’s moral development across a range of different moral transgressions. Taking up prior research that showed morality and intelligence to be related in adolescents and adults, the current study wants to test if these findings can be extended to younger children. The study was designed to address some of the shortcomings in prior research by examining young children aged between 6 years; 4 months and 8 years; 10 months, using a broad concept of moral development including emotional aspects and applying an approach that is closely connected to children’s daily lives. Participants (N = 129) completed a standardized intelligence test and were presented four moral transgression stories to assess moral development. Results demonstrated that findings from prior research with adolescents or adults cannot simply be extended to younger participants. No significant correlations of moral development and intelligence were found for any of the presented stories. This provides first evidence that – at least in middle childhood – moral developmental status seems to be independent from children’s general intelligence assessed by figural inductive reasoning tests.